Sulfonated Chitosan and HKUST‐1 metal organic frameworks based hybrid membranes for direct methanol fuel cell applications. Issue 36 (27th July 2022) - Divya, Kumar; Sri Abirami Saraswathi, Meenakshi Sundaram; Nagendran, Alagumalai; Rana, Dipak
Abstract: Sulfonated Chitosan and copper‐based metal–organic frameworks (Hong Kong University of Science and Technology (HKUST‐1) or Cu‐BTC or MOF‐199) based hybrid membranes are fabricated using a solution casting method for direct methanol fuel cell (DMFC) applications. The well‐defined cubic structure and sharp crystalline X‐ray diffraction pattern confirms the successful synthesis of HKUST‐1. The SEM cross‐sectional images showed that incorporated HKUST‐1 acts as a pore‐filling agent as well as creating finger‐like hydrophilic channels into the S‐Chitosan matrix. The existence of intermolecular hydrogen bonding between the COOH groups of HKUST‐1 and SO3 H groups of S‐Chitosan enhances the membrane performances such as water uptake, ion exchange capacity, proton conductivity, and thermal stability. Specifically hybrid membrane with 0.5 wt% of HKUST‐1 showed the highest proton conductivity of 5.38 × 10 −3 and 6.19 × 10 −3  S cm −1 at 25 and 80°C respectively. Besides the S‐Chitosan‐0.5 membrane exhibited lower methanol permeability and selectivity than pristine S‐Chitosan and commercial Nafion membranes due to the small ionic size. Besides the pore reduction ability of HKUST‐1 selectively allowed protons and block the methanol permeation in the membrane matrix. Overall results indicate that the S‐Chitosan‐0.5 hybrid membrane is a suitable candidate for DMFC applications. Abstract : High performance S‐Chitosan/HKUST‐1 membranes.